2022
DOI: 10.1038/s41598-022-10903-8
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial work index during normal dobutamine stress echocardiography

Abstract: Dobutamine stress echocardiography is an alternative method to exercise stress echocardiography for the evaluation of ischemia. Recently, the novel speckle tracking imaging derived parameter, myocardial work index, was suggested for the evaluation of cardiac performance and was evaluated during exercise stress echocardiography. In this study, we analyzed the effect of dobutamine on myocardial work index variables during normal dobutamine stress echocardiography. Echocardiography examinations of patients with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The number of individual patients who responded was not given 49 . Another study on hyperbaric oxygen has shown an improvement in left ventricular function 50 . There was an enthusiastic report in a national newspaper.…”
Section: Long Covidmentioning
confidence: 99%
“…The number of individual patients who responded was not given 49 . Another study on hyperbaric oxygen has shown an improvement in left ventricular function 50 . There was an enthusiastic report in a national newspaper.…”
Section: Long Covidmentioning
confidence: 99%